Soil Fertility Analysis with Soil Microorganism Indicators - Febrianti Rosalina; sukmawati sukmawati (UNIVERSITAS NEGERI PADANG, 2022)
Areca nut and sago are typical fruits of the Papuan Community which produce waste. Utilization of waste for the community itself has not been done optimally, especially in agriculture. One way to overcome the problem of soil fertility is by adding organic matter. Areca nut shell waste and sago stem waste are alternative uses of existing waste by processing it into liquid organic fertilizer (POC) and biochar. Adding organic matter to the soil can increase soil productivity and fertility and can affect soil biological properties by increasing the activity of soil biota which play a role in breaking down and decomposing organic matter so that soil biological properties increase. The purpose of this study was to compare the biological properties of the soil applied with biochar and liquid organic fertilizer (POC) derived from areca nut shell and sago bark waste. The research method consisted of a completely randomized design (CRD) which consisted of 7 treatment levels. The first treatment (SB0) was control (without adding biochar), the second treatment (SB1) was areca nut shell waste biochar, the third treatment (SB2) was sago stem waste biochar, the fourth treatment (SB3) was a combination of areca nut shell and stem biochar. sago, the fifth treatment (SB4) was POC of areca nut shell waste, the sixth treatment (SB5) was POC of sago stem waste, and the seventh treatment (SB6) was a combination of POC of areca nut shell waste and sago stems. The parameters of this study included determining the total bacterial population, total fungal population, soil respiration, organic matter activity, nitrogen fixing activity, pH, Organic-C, and Total-N. Based on the results of the research that has been done, it can be concluded that the treatment in the form of biochar and POC in general has a significant effect on increasing soil pH, Organic-C, Total-N, total bacterial population, total fungi population, soil respiration, Nitrogen fixing activity, and The activity of organic matter. Treatment with biochar (SB1, SB2, and SB3) gave the highest average microbial population which was directly proportional to the respiration rate.Pinang dan sagu merupakan buah khas masyarakat Papua yang menghasilkan limbah. Pemanfaatan limbah bagi masyarakat itu sendiri belum dilkakukan secara optimal, terutama di bidang pertanian. Salah satu cara untuk mengatasi masalah kesuburan tanah adalah dengan pemberian bahan organik. Limbah kulit buah pinang dan limbah batang sagu menjadi alternatif pemanfaatan limbah yang ada dengan diolah menjadi pupuk organik cair (POC) dan biochar. Pemberian bahan organik ke dalam tanah dapat meningkatkan produktivitas dan kesuburan tanah serta dapat mempengaruhi sifat biologi tanah dalam meningkatkan aktivitas biota tanah yang berperan dalam merombak serta mendekomposisi bahan organik sehingga sifat biologi tanah meningkat. Tujuan dari penelitian ini adalah untuk membandingkan sifat biologi tanah yang diaplikasikan dengan biochar dan pupuk organic cair (POC) yang berasal dari limbah kulit buah pinang dan kulit batang sagu. Adapun metode penelitian ini terdiri dari Rancangan Acak Lengkap (RAL) yang terdiri dari 7 taraf perlakuan. Perlakuan pertama (SB0) adalah control (tanpa pemberian biochar), perlakuan kedua (SB1) adalah biochar limbah kulit buah pinang, Perlakuan ketiga (SB2) adalah Biochar limbah batang sagu, Perlakuan keempat (SB3) adalah kombinasi Biochar limbah kulit buah pinang dan batang sagu, perlakuan kelima (SB4) adalah POC limbah kulit buah pinang, Perlakuan keenam (SB5) adalah POC limbah batang sagu, dan Perlakuan ketujuh (SB6) adalah kombinasi POC limbah kulit buah pinang dan batang sagu. Parameter dari penelitian ini meliputi penetapan total populasi bakteri, total populasi fungi, respirasi tanah, Aktivitas perombak bahan organic, aktivitas penambat Nitrogen, pH, C-Organik, dan N-Total. Berdasarkan hasil penelitian yang telah dilakukan dapat disimpulkan bahwa pemberian perlakuan berupa biochar dan POC secara umum memberikan pengaruh yang nyata terhadap kenaikan pH tanah, C-Organik, N-Total, total populasi bakteri, total populasi fungi, respirasi tanah, aktivitas penambat Nitrogen, dan Aktivitas perombak bahan organic. Perlakuan dengan pemberian biochar (SB1, SB2, dan SB3) memberikan rata-rata populasi mikroba tertinggi yang berbanding lurus dengan laju respirasinya.